Keefektifan Pembelajaran Menulis Cerpen Bertema Inklusi Sosial yang Berbantuan Media AI Story Mapping dan Canva Storyboard dengan Model PjBL - Mafaza, Azki Akhmad; Zuliyanti, Zuliyanti (Paedagogie, 2026)
This study aims to examine the effectiveness of AI Story Mapping and Canva Storyboard as learning media in teaching short story writing with social inclusion as the thematic focus, and compare the effectiveness of the two media. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. Data were collected from pretest and posttest scores, supported by classroom observations and interviews. The research sample consisted of two classes. Data collection was conducted through written tests, observations, and interviews. Data analysis techniques included statistical procedures such as the normality test, homogeneity test, paired-sample t-test, N-Gain analysis, and independent-sample t-test. The results showed that the average N-Gain percentage for the AI Story Mapping media was 63.2363%, while the Canva Storyboard media achieved an average of 64.5803%. These findings indicate that both learning media demonstrated a moderate level of effectiveness and were categorized as quite effective. Furthermore, the difference in effectiveness between the two media was approximately 1.34%. In conclusion, both AI Story Mapping and Canva Storyboard are equally effective for teaching short story writing, with no significant difference in their effectiveness.